种低成本瓷砖胶粘剂及其制备方法 (2019)
种低成本瓷砖胶粘剂，其特征在于，包括如下重量份的组分：硅酸盐水泥15～25份；河砂30～42份；陶瓷砖抛光废渣20～35份；可再分散性胶粉1～2份；保水剂0.1～0.5份。制备瓷砖胶粘剂的方法，包括如下步骤：1)将水泥和陶瓷砖抛光废渣投入高速混合打粉机中进行破碎分散和混匀的预混合过程；2)将河沙、可再分散性胶粉和保水剂加入到1)中，并混合均匀。本发明制备的瓷砖胶粘剂，有效解决现有技术中工业废渣的添加量小和胶粘剂成本高的问题，利用陶瓷砖抛光废渣具有火山灰活性，以其作为水泥混合材，尽可能多的添加陶瓷砖抛光废渣，降低水泥用量，增加胶粘剂的保水性和可塑性，提高胶粘剂的抗压强度和抗折强度。 The invention provides a tile adhesive with low cost. The adhesive is characterized in that the adhesive comprises the following components in parts by weight: 15-25 parts of Portland cement, 30-42 parts of river sand, 20-35 parts of ceramic tile polishing waste residues, 1-2 parts of redispersible rubble powder, and 0.1-0.5 parts of a water-retaining agent. The method for preparing the tile adhesive comprises the following steps: (1) cement and ceramic tile polishing waste residues are added into a high speed mixing and powder producing machine in order to carry out fragmentation, dispersion, and well mixing for premixing; (2) the river sand, the redispersible rubble powder and the water-retaining agent are added into t